Penilaian Kinerja Pramusaji di Hotel Laguna Bintan - Enjelita Putri Sebina; Nova Eviana (LPPM and Travel Operation Department Universitas Asa Indonesia, 2024)
Employees performances have positive contribution the business performance and sustainalibility. Considering the importance of employee performance, the evaluation of employees performances have a significant role for management. This study aims to evaluate the waiters’ performance at Laguna Bintan Hotel. Data were collected through the restaurant leader’s performance evaluation toward all waiters. Data were analyzed with the mean score. The results showed that the waiters of Laguna Bintan Hotel have good performances. The management therefore keep maintaining waiter performance by enhancing their sense of initiative.